Analysis on Efficacy of Chitosan-Based Gel on Bone Quality and Quantity - Jayash, Soher Nagi; Hashim, Najihah Mohd; Misran, Misni; Ibrahim, Norliza; AL-Namnam, Nisreen Mohammed; Baharuddin, N. A. (Frontiers in Materials, 2021)
Objective: To assess and compare the quantity and the quality of the newly bone generated when using chitosan-based gel scaffold and osteoprotegerin-chitosan gel scaffold. Methods: A total of 18 critical‐sized defects on New Zealand white rabbit craniums were created. In twelve defects, either chitosan gel or osteoprotegerin-chitosan gel was implanted the last 6 defects were kept unfilled as a control. Bone formation was examined at 6 and 12 weeks. Bone’s specimens were scanned using the High-resolution peripheral quantitative computed tomography. Histological and histomorphometric analysis were carried out to compare the volume and area of regenerated bone. Results: The results of the HR-pQCT showed that bone volume and densities in the osteoprotegerin-chitosan gel group were significantly higher than the chitosan gel and control groups whereas, the bone volume density in the chitosan gel group was significantly higher than the control group in both intervals time (p = 0.01, p= =000). No significant difference in bone volume between the chitosan gel and control groups (p =0.506, p=0.640) was observed. However, similar findings were shown in the histomorphometric analysis, with the highest new bone formation was observed in the OPG-chitosan gel group followed by the chitosan group. The mean percentage of new bone was greater at 12 weeks compared to 6 weeks in all groups. Conclusion: Chitosan-based gel demonstrated a significant bone quantity and quality compared to unfilled surgical defects. Consistently, osteoprotegerin enhanced the chitosan gel in bone regeneration.